Isokinetic Assessment of Shoulder Joint Strength Ratios in Male Recreational Weightlifters: A Cross-Sectional Study - Osama R. Abdelraouf; Marwa Y. Ebrahim; Amr A. Abdel-aziem; Soheir M. Abdel-Rahman; Ahmed S. Yamani; Ahmad A. El Askary (Applied Bionics and Biomechanics)
Background. Isokinetic strength imbalance is a risk factor for movement dysfunctions and injuries related to shoulder complex. The effects of recreational weightlifting on developing the imbalances between the shoulder muscles are not yet known. Objectives. To investigate the isokinetic concentric shoulder muscle strength values (peak torque normalized to body weight) in recreational weightlifters (RWL) and to compare the shoulder muscles agonist/antagonist ratios with nonweightlifters. Methods. Thirty male RWL with mean age, weight, height, and body mass index (BMI) of 21.56 years, 84.25 kg, 175.34 cm, and 26.51 kg/m2, respectively, matched with nonweightlifters served as a control group. The normalized concentric peak torque values of shoulder flexors, extensors, abductors, adductors, and internal and external rotators were measured at angular velocity 120°/sec by using Biodex isokinetic system. Moreover, the agonist/antagonist strength ratio for all muscle groups were calculated. Results. The normalized peak torques of RWL group were significantly greater than the control group (p<0.05). The abductor/adductor and external rotator/internal rotator ratios of the RWL were significantly lower than the control group (p=0.008 and 0.009, respectively). Conversely, there was no significant difference between both groups in relation to the flexor/extensor ratio (p=0.259). Conclusion. These results suggested that the recreational weightlifting exercises place trainees at risk of muscle imbalances. Therefore, the restoration of a normal concentric abductor/adductor and external rotator/internal rotator strength ratios may decrease the risk of possible shoulder injury.